The Relationship Between Family Support and Adherence to Hypertension Care Among Older Adults in a Rural Community - Tahan Tahan; Imran Saputra Surabakti; Siti Nurmawan Sinaga; Eko Murdianto; Wara Valegis; Vina Enita Noviani (Asosiasi Dosen Muda Indonesia, 2026)
Hypertension is often referred to as a silent killer because many individuals are unaware of their elevated blood pressure until serious complications occur. This condition is particularly concerning among older adults due to age-related physiological changes that increase vulnerability to chronic diseases. Objective: This study aimed to analyze the relationship between family support and adherence to hypertension care among elderly individuals in Bangun Rejo Village, highlighting the importance of family involvement in chronic disease management. Methods: This research used a quantitative approach see more with a descriptive correlational design and cross-sectional method. A total of 91 respondents were selected using total sampling. Data were collected through structured questionnaires measuring family support and adherence to hypertension care, and analyzed using descriptive statistics and the Chi-Square test. Results: The results showed that most respondents were aged over 66 years (51.6%) and predominantly male (71.4%). Half of the participants reported good family support (50.5%), while the majority demonstrated low adherence to hypertension care (59.3%). Statistical analysis revealed a significant relationship between family support and adherence (p-value < 0.05). Implications: These findings indicate that strengthening family involvement can improve adherence to hypertension treatment among elderly individuals. Family-centered interventions and education programs in primary healthcare settings are recommended to enhance disease management outcomes. Originality: This study provides localized empirical evidence from a rural community, emphasizing the role of family support in influencing treatment adherence among older adults. It contributes to the development of context-specific strategies for family-based chronic disease management.